It Was the Wind - H. C. Palmer (Symphony in the Flint Hills, 2012)
A poem about the seasons in Flint Hills, Kansas, circa 1936.
Keywords: Flint Hills; poem; poetry; poet; story; Kansas; cattle; wildlife; summer